Work Status, Satisfaction and Organizational Citizenship Behavior: A Case Study on Bangka Islamic Bank, Province of Bangka Belitung - Hamsani, Hamsani; Valeriani, Devi; Zukhri, Nizwan (International Review of Management and Marketing, 2019)
Permanent employees and contract employees plays an important role in the company. Therefore, every company must keep and maintain all the employees in order to be able to contribute as expected by the company. Good employees are not only able to do their duties and responsibilities, but willingly able to demonstrate an attitude beyond their duties and responsibilities as a form of sympathy to colleagues and companies. Attitude shown by employees voluntarily, without coercion and not related to salary or reward system, better known as organizational citizenship behavior (OCB). In the face of increasingly fierce competition, especially the banking sector, which is closely related to the ability of employees serving customers, OCB attitude that employees are needed to win the competition. But not easy to create the attitude of OCB employees. Many factors affect the attitude of OCB, such as work status and level of employee satisfaction. The purpose of this article to examine whether work status (permanent and contract) have a different level of satisfaction? Is there any difference OCB attitude shown by employees permanent and contract? Whether employee satisfaction has significant positive effect on the attitudes of employees OCB? Especially social satisfaction, extrinsic satisfaction (ES), and intrinsic satisfaction (IS). By using the 49 employees (30 permanent and 19 contract), Islamic Bank of Bangka, using descriptive quantitative analysis, the results showed that there was no difference in satisfaction and OCB attitudes among permanents employees and contract. Regression results indicate that social satisfaction and ES has a positive relationship to the attitude of OCB employees but not significant because P > 0.05 (respectively 0.075 and 0.07). IS showed a negative and significant relationship to the OCB (P < 0.05 level). However the results of ANOVA test, the all of employees satisfaction (social satisfaction, ES, IS) has a positive and significant relationship to the OCB, P < 0.05 level (0.029). Keywords: Work Status, Social Satisfaction, Extrinsic Satisfaction, Intrinsic Satisfaction, Organizational Citizenship Behavior JEL Classifications: D23, J28, J62 DOI: https://doi.org/10.32479/irmm.7838